Development of biology learning videos based on problem-based learning on the digestive system topic to improve the health literacy of high school students - Fadhilla, Nadia Alima; Pratama, Anggi Tias (Universitas Negeri Yogyakarta, 2026)
This research aims to develop Problem-Based Learning-based learning video media on the topic of the digestive system that can improve the health literacy of high school students, especially class XI MIA, and assess the feasibility of the developed learning video media. This research is based on the fact that the level of health literacy of high school students in Indonesia is still low, and classroom learning is still not directed to improve students’ health literacy, so it is necessary to develop a learning medium that can help improve the health literacy of high school students, especially class XI MIA. The type of research used in this study is development research (RD), which follows the 4D development model by Thiagarajan (1974), modified into 3 stages: Define, Design, and Development. The research instruments include interview guidesheets and product feasibility assessment questionnaires, with a 1-5 Likert scale. The research data were then analyzed using descriptive techniques. The research produced a biology learning video based on Problem-Based Learning on the human digestive system to help students improve their health literacy. The results of the study also showed that the assessment by material experts of all aspects of the developed learning video obtained a media feasibility percentage of 100%. The assessment by media experts from all aspects obtained a feasibility percentage of 88.46%. The average percentage of eligibility, based on assessments by material and media experts, falls within the “Very Feasible” category. This means that the video media of biology learning based on Problem-Based Learning on the topic of the digestive system is suitable for use in learning. The results of this study show that the development of PBL-based video media can be a strategic alternative for biology learning, integrating concept mastery with improvements in students’ health literacy.